2021
DOI: 10.1007/s00784-020-03648-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the additional use of subgingival air polishing with erythritol powder in the treatment of periodontitis patients: a randomized controlled clinical trial

Abstract: Objectives To date, scarce evidence exists around the application of subgingival air polishing during treatment of severe periodontitis. The aim of this study was to evaluate the benefits of subgingival air polishing during non-surgical treatment of deep bleeding pockets in stages III-IV periodontitis patients Materials and methods Forty patients with stages III-IV periodontitis were selected, and pockets with probing depth (PD) 5-9 mm and bleeding on probing (BoP) were selected as experimental sites. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…It can be assumed that (i) in multi-rooted teeth the extensive use of antiseptics with high substantivity (chlorhexidine) could in part compensate the impaired mechanic accessibility of furcation regions, and (ii) additional air-polishing might have particular benefits in moderate pockets.Application of erythritol air-polishing in addition to conventional instrumentation for non-surgical therapy has recently been investigated by three groups. WhilePark et al (2018) andMensi et al (2021) could not prove any clinical advantages over SRP,Jentsch et al (2020) showed a higher reduction of residual periodontal pockets with PPD ≥5 mm after 6 months compared to SRP alone. Differences in the study design and the definition of experimental sites might explain the inhomogeneous outcomes.…”
mentioning
confidence: 70%
“…It can be assumed that (i) in multi-rooted teeth the extensive use of antiseptics with high substantivity (chlorhexidine) could in part compensate the impaired mechanic accessibility of furcation regions, and (ii) additional air-polishing might have particular benefits in moderate pockets.Application of erythritol air-polishing in addition to conventional instrumentation for non-surgical therapy has recently been investigated by three groups. WhilePark et al (2018) andMensi et al (2021) could not prove any clinical advantages over SRP,Jentsch et al (2020) showed a higher reduction of residual periodontal pockets with PPD ≥5 mm after 6 months compared to SRP alone. Differences in the study design and the definition of experimental sites might explain the inhomogeneous outcomes.…”
mentioning
confidence: 70%
“…From the eight included studies (Table 2), four trials 19,26,27,29 were conducted during the SPT phase, and four trials 22–25 were conducted during the APT. Five RCTs 19,22–24,27 followed a parallel design, whereas three 25,26,29 used a split‐mouth design.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum mean age was 44.3 years, 23 and the maximum mean age was 61 years 26 . Seven studies included smokers 19,22–24,26,27,29 ; however, in two of these studies, individuals smoking more than 7 24 and 10 23 cigarettes per day were excluded. In the remaining study, 25 inclusion or exclusion of smokers was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, promising effects in terms of titanium cleaning efficacy were seen (Tastepe, et al, 2018;Drago, et al, 2017). When erythritol air-polishing was compared to scaling and rootplaning in periodontal maintenance studies and in non-surgical periodontitis treatment studies, comparable clinical and microbiological results were found Hägi, et al, 2015;Park, et al 2018;Jentsch, et al, 2020;Mensi, et al, 2021). More recently, a study by Cosgarea et al (2021) showed that erythritol air-polishing during periodontal surgery may represent a valuable adjunct following calculus removal or as minimally invasive treatment for root surfaces without calculus.…”
Section: Introductionmentioning
confidence: 97%